Insights into coaching a women's national futsal team - Carson, Fraser; Nemčić Bojić, Tihana; Bahdur, Khatija (Frontiers in Sports and Active Living, 2025)
IntroductionTournament coaching is known to provide different challenges to coaching a team across a regular season. There is limited time to prepare, meaning that team roles and objectives need to be established quickly, and communication must be effective.MethodThis interpretive ethnographic case study explored how the coach of a women's national futsal team approached this, while competing at a week-long tournament in preparation for a World Cup qualification event.ResultsFollowing the completion of five interviews (one prior to, three during, and one post tournament), thematic coding produced three main themes: (1) Keeping consistency in development and focus, (2) Communicating openly, and (3) Individualizing approaches.DiscussionThe coach established a clear goal for the tournament, with the focus on the team's game plan and ability to implement the tactics they want at the World Cup, which helped create performance targets that were independent of the results to help maintain consistency. A transformative leadership style, underpinned by free communication empowered the players to buy into the system and enhanced motivation and commitment. The coach, with her staff, made a deliberate effort to spend time individually with players, as this allowed players to create autonomy, which enhanced commitment. The findings provide insights for coaching women's teams in general and add further information about coaching in an idiosyncratic tournament environment.